Penegakan Hukum Pidana Terhadap Pelaku Tindak Kampanye Hitam (Black Campaign) di Media Sosial - Mhd Teguh Syuhada Lubis (Fakultas Hukum Universitas Riau, 2022)
The purpose of this study is to determine the form of black campaign crime according to the Indonesian regional head election law, the mechanism of investigation of the perpetrators of the black campaign crime of regional head elections based on the regional head election law and the information and transaction law, and criminal liability for the perpetrators of the regional head election black campaign based on election law and information and transaction law. The research conducted is normative juridical research using secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of the study, it is known that the form of black campaign crime according to the regional head election law is in the form of inciting slandering and playing against each other, then it can also be in the form of defamation, insulting and disseminating information with the aim of causing hatred to political opponents mentioned in information and transaction law. The mechanism of investigation of the perpetrators of the black campaign crime of the regional head election based on the regional election law and the information and transaction law is that in essence police investigators can conduct investigations after reports of election violations are received by the provincial election supervisory and regency election supervisory.